Maternal Age Correlates with Stunting in Children: Systematics Review - Astuti, Fardhiasih Dwi; Azka, Arlina; Rokhmayanti, Rokhmayanti (Journal of Maternal and Child Health, 2022)
Background: Teenage mother should be ready for the consequences to come. It is important to get prepared both mentally and economically. A teenage mother and her offspring are at risk of malnutrition and stunting. This study aims to analyze the correlation between maternal age and the incidence of stunting based on published articles. Subjects and Method: A systematic review was conducted to find the correlation between maternal age and the incidence of stunting. The research was conducted by seeking into the database by using PubMed, Ebsco, Google Scholar, and SpringerLink. The keywords used were "risk factor" OR “determinant” AND “stunting” AND "young maternal age" OR "adolescent mother*" OR "teen mother*" OR "adolescent pregnancy" OR "teen pregnancy" AND "logistic regression" OR “multivariate”. The obtained articles underwent screening and conformity assessment. Articles that met the criteria were subsequently extracted. Results: 1,048 articles were discovered from PubMed, Ebsco, Google Scholar and SpringerLink databases and 9 of them were included in the review. The articles were from Turkey, Tanzania, Pakistan, Ghana, Uganda, Burundi, 2 articles were from Ethiopia, and 1 article covered Brazil, Guatemala, India, Philippines, and South Africa. The prevalence of stunting in each region from the obtained articles showed a variation from 13.8% - 79.5%. It discovered the correlation between maternal age during pregnancy and incidence of stunting that pregnant women under the age of 20 were at greater risk for stunting compared to women aged ≥ 20 years (OR 1.37 – 7.56). Women at a younger age were at greater risk of having stunting children. Conclusion: The correlation between maternal age during pregnancy and stunting indicates that the younger the mothers, the higher the risk for stunting. The risk for stunting will decrease with the increasing maternal age at the time of delivery. Keywords: adolescence, stunting, teenage mothers, maternal age Correspondence: Fardhiasih Dwi Astuti. Jl. Prof. DR. Soepomo Sh, Warungboto, Umbulharjo, Yogyakarta, Special Region of Yogyakarta. Email: Fardhiasih.dwiastuti@ikm.uad.ac.id.